Efficacy and safety of Vildagliptin in the management of type 2 Diabetes Mellitus - H Md., Iftekar; V, Kalaiselvan; N S, Gyanendra (Indian Journal of Pharmacy Practice)
Type 2 diabetes mellitus (T2DM) is epidemic in most developed and many developing countries and is a leading cause of morbidity and mortality. Vildagliptin represent a new class of oral anti-diabetic agent that enhance the action of incretin hormone through inhibition of Dipeptidyl peptidase-4. The enhancement of incretin hormone (GLP-1 & GIP) potentiates the insulin secretion in β-cells and suppresses the glucagon release by α-cells in the pancreas. The present article reviews the impact of DDP-4 inhibitor, Vildagliptin in monotherapy as well as combination with a special emphasis on the Risk & Benefits on different organs of T2DM patients. Literature was searched on PubMed related to safety and efficacy of vildagliptin that include all the observational and interventional studies. Vildagliptin is a potent & specific DPP-4 inhibitor that has demonstrated weigh neutrally, and improves β-cell as well as cardiovascular function in patient with DM type 2 in multiple monotherapy & combination. However, hypoglycaemic event reported with combination of metformin, rosiglitazone and SU, but safe with pioglitazone, while in combination with insulin the event was found to be reduced. Vildagliptin also shows feedback inhibition of GLP-1 secretion which reduces risk of cardiovascular and hypoglycaemia, whereas it concern to increasing the risk of pancreatitis according to post marketing surveillance.
Keywords: Vildagliptin; DPP-4 inhibitor; T2DM; Incretin hormone; GLP-1& GIP